2017
DOI: 10.1007/s11701-017-0750-9
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery for the base of tongue squamous cell carcinoma: a preliminary comparison between da Vinci Xi and Si

Abstract: Considering the emerging advantages related to da Vinci Xi robotic platform, the aim of this study is to compare for the first time the operative outcomes of this tool to the previous da Vinci Si during transoral robotic surgery (TORS), both performed for squamous cell carcinomas (SCC) of the base of tongue (BOT). Intra- and peri-operative outcomes of eight patients with early stage (T1-T2) of the BOT carcinoma and undergoing TORS by means of the da Vinci Xi robotic platform (Xi-TORS) are compared with the da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Although Gorphe et al state that with the Xi, DT for TORS is dramatically shortened, 13 only Alessandrini et al really compared DT between the Si and Xi platforms and found no difference in mean DT (19.00 min, SD 5.37 vs. 16.22 min, SD 6.42, p = 0.388). 14 Additional Xi advantages are smaller/longer robotic arms with additional joints, and a patient clearance button, allowing the bulky joints to rotate. Together, these improvements potentially reduce arm collisions and instrument "chopsticking."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Gorphe et al state that with the Xi, DT for TORS is dramatically shortened, 13 only Alessandrini et al really compared DT between the Si and Xi platforms and found no difference in mean DT (19.00 min, SD 5.37 vs. 16.22 min, SD 6.42, p = 0.388). 14 Additional Xi advantages are smaller/longer robotic arms with additional joints, and a patient clearance button, allowing the bulky joints to rotate. Together, these improvements potentially reduce arm collisions and instrument "chopsticking."…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated by a significantly shorter Xi console time for BOT resection compared to the Si (28.53 min, SD 4.46 vs. 34.00 min, SD 4.22, p = 0.024). 14 Also, in their Xi experience, Gorphe et al rarely encounter "chopsticking," and surely less than with the Si system. 13 When trying to reach the larynx or hypopharynx, however, other authors report that the 8-mm Xi instruments lead to crowding in the operating field with a reduced visibility, decreased agility of the wrist motion, increased internal collisions, and more frequent need for repositioning, slowing down the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, most studies have compared robotic with open or endoscopic surgery, with few studies assessing the suitability of different robotic models or determining the optimal model for types of operation. Moreover, most previous studies have assessed the use of robotic surgery on diseases of the stomach and colon, and in urology and obstetrics and gynecology, with few studies assessing the use of robotic surgery on the thyroid gland [6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the da Vinci Si and Xi systems for transoral robotic thyroidectomy showed that the Xi system resulted in better patient outcomes, including reductions in postoperative pain and hospital stay and fewer complications, although the surgical and console times were similar [11]. By contrast, overall operation and console times were significantly shorter in patients who underwent transoral robotic surgery for tongue cancer using the da Vinci Xi than the Si system [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, photoacoustic imaging is a new method that offers in-depth visualization possibilities, up to 10 cm, of fluorescent nano-bio sensors using ICG [61]. Currently, a robotic DaVinci system equipped with a camera with fluorescence filters suited for ICG imaging is available [62]. Imaging of cell stress combined with the possibility of action enables more nuanced individual options in the future for treating tumors throughout the tumor progression.…”
Section: Discussionmentioning
confidence: 99%